Identification of Knowledge about Pulmonary Tuberculosis in Bulota Village, Limboto District, Gorontalo Regency - Paramata, Nanang Roswita; Rahma, ST (Universitas Negeri Gorontalo, 2026)
An estimated 10.6 million people fall ill with tuberculosis worldwide. Based on data from the 2023 Global Tuberculosis Report published by the WHO, Indonesia ranks second in the world in terms of the highest number of tuberculosis cases. In 2022, Indonesia accounted for about 10% of the total global TB cases, with an estimated 969,000 new cases. Data from the Gorontalo Provincial Health Office shows that Gorontalo ranks 15th in Indonesia with a prevalence of 68%. There are 6,949 patients. Gorontalo Regency has the highest number of patients, with 2,310 people as of 2025. Data from the Gorontalo Regency Health Office shows that Limboto District has the highest prevalence of pulmonary tuberculosis patients. Currently, various efforts have been made in Gorontalo, including health education, but researchers feel that there are still groups of people who need special treatment for several reasons, including the low level of education and knowledge of the community. Therefore, researchers are interested in studying the extent of the community's knowledge about tuberculosis so that the government can take strategic steps to increase public knowledge about tuberculosis. The purpose of this study was to determine the level of knowledge about pulmonary tuberculosis in Bulota Village, Limboto District, Gorontalo Regency. The method used in this study was a quantitative descriptive method to identify the community's knowledge about pulmonary tuberculosis. The results obtained in this study show that out of a total of 50 respondents, 19 people (38%) were in the good category, 27 people (54%) were in the adequate category, and 4 people (8%) were in the poor category. Thus, the knowledge of the community in Bulota Village, Limboto District, Gorontalo Regency is mostly in the adequate category. With these results, there is a need for new breakthroughs in the form of methods that are more interesting and closer to the community to increase public knowledge so that it improves to good.